Comparison of active self-ligating brackets and conventional pre-adjusted brackets - Hamilton Robert; Goonewardene Mithran S.; Murray Kevin (Australasian Orthodontic Journal, 2023)
Active self-ligating brackets may be more efficient than conventional pre-adjusted brackets.